CLASSROOM MANAGEMENT AND THE IMPLICATIONS TO QUALITY OF LEARNING - Sulaiman, Sulaiman (Jurnal Ilmiah Peuradeun, 2015)
The aims of this study is to determine the educative rules in classroom, educational interaction in the classroom, students' mental engagement in learning, learning behavior and the strategies to build a classroom climate in creating effective learning in Madrasah Aliyah in Aceh. The method used is qualitative method. The subjects were all over the Madrasah Aliyah in Aceh. While the sampling technique in this research was done by using purposive sampling to 9 Madrasah Aliyah in Aceh. The results showed that the management of physical condition classes have not been effective, while non-physical classroom management (socio-emotional) showed effective. In addition, the ability of teachers to educational interaction in the classroom showed not optimal. Strategy to build a classroom climate in creating effective learning in Aceh At the Madrasah Aliyah influence on the quality of learning and satisfaction (climate) study.